Expanding Pharmacists' Scope of Practice to Include Immunization in Nova Scotia - Beth O'Reilly; Jennifer Isenor; Susan Bowles (McMaster University Library Press, 2017)
On 10 December 2010 An Act to Amend Chapter 36 of the Acts of 2001, the Pharmacy Act (Bill 7) received Royal Assent in Nova Scotia, including an amendment that enabled an expanded scope of pharmacy practice.  Expanding pharmacists' scope of practice came about from recommendations by various federal and provincial government bodies as an attempt to improve accessibility to health care and decrease costs. In 2013, pharmacists in Nova Scotia began administering the influenza vaccine as part of the publicly funded program in attempts to improve vaccine coverage rates. Preliminary evaluation in Nova Scotia has shown an increase in influenza vaccination coverage. Although pharmacist administration of influenza vaccination may improve vaccination coverage and reduce demand on physician time, there may be tension created among the professions, which needs to be addressed and managed.  La modification des lois qui concernent les professions de santé réglementées, An Act to Amend Chapter 36 of the Acts of 2001, the Pharmacy Act (Loi 7), a été sanctionée en Nouvelle-Écosse le 10 Décembre, 2010. Un de ces changements législatif avait pu renforcer l'élargissement du practique des pharmaciens en Nouvelle-Écosse. Grâce a la conseil de plusieurs groupes gouvernementale, Fédérale et Provinciale, cette élargissement de practique essaient a diminuer le coût et ameliorer l'accessibilité du système de santé. En 2013, les pharmaciens en Nouvelle-Écosse ont commencé d'administrer le vaccin antigrippal gratuitement au public, pour augmenter le taux d'immunisation contre la grippe dans le province. Une évaluation préliminaire a démontré l'augmentation des taux d'immunisation en Nouvelle-Ecosse. Bien que l'administration du vaccin contre la grippe pourrait améliorer la couvrage vaccinale et reduire le temps des médecins, il pourrait aussi crée des tensions entre les professions medicaux, qui doit être addresser et gérer.